Scale Analysis of Blocking Events from 2002 to 2004: A Case Study of an Unusually Persistent Blocking Event Leading to a Heat Wave in the Gulf of Alaska during August 2004 - H. Athar; Anthony R. Lupo (Advances in Meteorology)
The climatology of northern hemisphere blocking events is presented assessing the relative contributions of the planetary and synoptic scales to 500 hPa heights in order to determine the proportion of blocks dominated by a single-scale. The heights were averaged over a region encompassing the block, and then compared with corresponding monthly mean values. If planetary-scale or synoptic-scale heights are greater than the monthly mean, the block is called single-scale dominant. In the study, 79% of blocks were single-scale dominant, whereas the remaining 21% of events were alternating-scale prominent. This proportion varied by season with winter (summer) events being synoptic (planetary) scale dominant. The stability of blocks is also examined to determine if two stability indicators were useful in the assessment of the character of planetary and synoptic-scale flows. These quantities are area integrated enstrophy, and the maximum value of stream function gradients within the block region. The analysis of a prolonged block occurring in the Gulf of Alaska during August 2004 shows the planetary-scale is unstable during block onset and then stabilizes during the mature stage. The synoptic-scale played a dominant role in destabilizing the planetary-scale during the mature stage of the block initiating decay.